Efektivitas Forum Group Discussion dan Video dalam Meningkatkan Pengetahuan Pencegahan Obesitas dan Gizi Seimbang di SMAN 2 Padalarang - Wityadarda, Carissa; Hardjanti, Maura; Victoria, Bernadette; Firmansyah, Yura Witsqa; Nurfadhilla, Nabilla Bilqi; Dewi, M Falah Putra; Immanuella, Ester Hanantika (Universitas Nusantara PGRI Kediri, 2025)
The 2017 Global Nutrition Report states that 2 billion adults and 41 million children worldwide are overweight or obese. Based on Body Mass Index (BMI) assessments using Z-scores, it was found that out of 168 students at SMAN 2 Padalarang, 21 students (12.5%) had abnormal BMI values. One proposed solution is nutrition education through Focus Group Discussions (FGDs) and learning videos to increase students' knowledge about obesity prevention and balanced nutrition. This program aims to determine whether there is a significant difference between the pre- and post-intervention scores for each method. The implementation of this activity involved FGDs and learning videos, with 248 students from grades 10, 11, and 12 at SMAN 2 Padalarang participating. A total of 124 students received counseling through the FGD method, while the other 124 students participated through the learning video method. This program was conducted on August 21-22, 2024. The analysis showed that both intervention methods, video and FGD, had a significant impact (p-value 0.000 for both interventions) on the change in scores from pre-test to post-test. In conclusion, in this program, the FGD method showed a greater effect (1.12) than the learning video (0.99).